ANALISIS TREND KEUANGAN: PADA PERUSAHAAN XYZ - tasya imelda tasya; Alsi Shintia Alsi; Nanda Mauliza Nanda; Salwa Aidilla Fitri Salwa; Pashya Niasty Putri Pasaribu Pashya; Hashifa Nuri; Mariana Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
This article discusses strategies for state financial management, emphasizing the critical role of government accounting in promoting efficiency, transparency, and fiscal accountability. In the context of public financial governance, government accounting functions as a tool to improve the quality of financial information through the application of reliable and consistent reporting standards. This study uses a literature review method, examining relevant regulations, government accounting standards, and best practices implemented in various countries. The findings indicate that proper implementation of government accounting can produce accurate and trustworthy financial reports, strengthen oversight of budget usage, and facilitate audit processes and fiscal policy evaluations. Furthermore, a well-established government accounting system enhances public trust in government institutions by increasing transparency in the management of public funds. This study recommends that governments strengthen institutional capacity for implementing accounting standards, improve the competencies of human resources, and promote the use of information technology in accounting processes. In conclusion, effective state financial management strategies can be achieved more efficiently and accountably through proper application of government accounting practices.